The Impact of Ownership Structure on Carbon Emission Disclosure in Energy Companies - Ni Made Dwicahyani; I Gusti Ayu Nyoman Budiasih (International Journal of Economics, Management and Accounting, 2025)
Carbon emissions in Indonesia continue to increase in line with the growing energy consumption needed to meet public demands. Energy sector companies, which contribute significantly to carbon emissions, are expected to take responsibility for their operational activities. One form of accountability is through carbon emission disclosure as a means of transparency to stakeholders. This study aims to examine the impact of institutional ownership, managerial ownership, and foreign ownership on carbon emission disclosure. The research objects are energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The study utilizes secondary data derived from annual reports, with a sample of 35 companies and 95 observations in total. Hypothesis testing was conducted using the t-test. The results indicate that institutional ownership and foreign ownership have a positive effect on carbon emission disclosure, while managerial ownership has a negative effect on carbon emission disclosure.